Archiv Peter Piller - Umschläge - Piller, Peter 1968- (Dashwood Books, 2014)
Contains 58 full-page reproductions of cover photographs from Armeerundschau, with textual portions removed; images on covers and on first and last pages are photomontages. Title information and limitation statement on label mounted on front cover; no other textual content
Umschlagtitel
Title from label mounted on front cover; edition statement and series statement from publisher's Web site
Published in an edition of 1,000 copies
"Printed in the Netherlands with production by Drukkerij Mart. Spruijt. Design by Hans Seeger"--Label mounted on front cover
One of the 5 monographs comprising the Dashwood Books series, volume 3, as described on the publisher's Web site, viewed March 17, 2016: http://www.dashwoodbooks.com/pages/events/26/dashwood-books-announces-new-dashwood-books
Keywords: Piller, Peter -- 1968-; Bildband